Implementasi Sistem Administrasi Perpajakan Modern Samsat Jawa Barat Ngabret (Samsat J’Bret) Sebagai Upaya Peningkatan Pendapatan Pajak Kendaraan Bermotor Di Samsat Kota Bekasi Tahun 2018-2020 - Surezna Rawi; Ratih Kumala (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to determine the implementation of the modern tax administration system of Samsat J'bret as an effort to increase motor vehicle tax revenue in the Bekasi City Samsat during the 2018-2020 period, the obstacles that arise and the efforts made by the Bekasi City Samsat in increasing motor vehicle tax revenues. This research is a descriptive research with a qualitative approach. The analytical method used is qualitative data analysis method. The results showed that the implementation of the modern tax administration system of Samsat J'bret as an effort to increase motor vehicle tax revenue in the Bekasi City Samsat in 2018-2020 was quite good in terms of resources, disposition and bureaucratic structure because in 2018-2020 motor vehicles tax revenue through the Samsat J'bret kept increasing. The obstacles that occur were that the public's understanding of Samsat J'bret services was still low and the facilities provided and the readiness of the system used were not yet comprehensive so that the system often went offline and experienced errors. Therefore, the Bekasi City Samsat needs to increase the campaign to the community, improve service facilities, and make system improvements so that errors no longer occur.